Penggunaan Set top box Bekas untuk Dimanfaatkan sebagai Cloud Server - Ardiansyah, Muhammad Fahri; Diansyah, Tengku Mohd; Liza, Risko (Ilmu Bersama Center, 2022)
The utilization of data storage media is currently very necessary to support the progress process in the digital era as it is today. One of the hardware needed to build personal data storage is HDD. But there are times when users need extra storage space using the internet or using the cloud. However, not all users can afford to rent or build an adequate server for securing personal data storage. Not all users need a server infrastructure that has high specifications to meet their needs. set top box is a device in the single-board computer category that is widely circulated in Indonesia. Set top box devices can be obtained at an affordable price, but can be a server. This research develops data storage based on a samba server application on a set top box device. Testing was done to change the default set top box operating system to the Linux operating system, the results showed that used set top box devices can be used as mini servers, the results of all the tests carried out obtained a result, namely a comparison of RAM and storage usage between the Pulpstone operating system and the system. armbian Linux operation has an increase in total RAM usage. Armbian Linux is greater than Pulpstone RAM usage which has an increase of 7.4% of the total RAM usage of the Pulpstone operating system, and data storage of the armbian Linux operating system has an increase of 74.4% from the data storage of the Pulsptone operating system, so Operating system changes can affect the total usage of RAM and data storage on the operating system used on the set top box device.